Integrated Tasks as a Means of Forming the Basic Competencies and General Abilities and Skills of Students - Normatova Gulnara (Researchparks Publishing, 2023)
In this article, some methodological aspects of the didactic conditions of the development and application of the system of interdisciplinary educational tasks for integrated lessons in primary education are considered. Therefore, the theoretical foundations of the creation of educational tasks, which provide internal and inter-subject connections in the educational process, have been drawn up.